Choices associated with automobiles for Men and Women: convergence or divergence? - Jato, Ricardo; Licht, René Henrique Götz (Review of Business Management, 2009)
The increase of the women purchase power has led some companies to adopt strategies of products differentiation as well as to produce specific products to the female public. The auto industry is not immune to this phenomenon, once the women represent, approximately, half of the automobile sales in the country. Considering the consumption and the behavior differences between women and men, it has set the following question: are there differences between the choices associated to the automobile by men and the choices associated to the automobile by women? It has been presented to the participants items found in the people’s day-by-day, which are valorized by them, and the participants have been asked to choose and associate these items to the automobile. The results analysis revealed there are more similarities than differences between choices associated to the automobile by men and choices associated to the automobile by women. The similarity between the choices suggests that the representations, the meanings and values assigned to the car by men and women are similar and thus the strategy of product differentiation does not apply to the automotive industry. Key words: Automobile. Marketing in the auto industry. Customer behavior. Differences between men and women.